[OP.1B.06] MIR-126 MODIFIED ENDOTHELIAL PROGENITOR CELLS TRANSPLANTATION CONTRIBUTES TO ANGIOGENESIS AFTER BRAIN FOCAL ISCHEMIA IN SHR RATS. (September 2017) - Huang, J.; Qu, M.; Lu, Y.; Gao, P.
Abstract : Objective: Transplantation of endothelial progenitor cells (EPCs) leads to better outcomes in experimental stroke, while improve the EPCs survival rate in ischemia area is still a challenge. MiR-126 modulates vascular development and angiogenesis. Here we overexpressed miR-126 in transplanted EPCs, to investigate the function of gene modified EPCs in angiogenesis after brain ischemia. Design and method: Adult male SHR rats underwent permanent suture middle cerebral artery occlusion (MCAO). One week after middle cerebral artery occlusion, the animals received tail vein injection of miR-126 modified EPCs as treatment or EPCs as control and were monitored for 5 weeks. Brain water content, infarct volume, neurological score, neurogenesis and angiogenesis were examined. Results: Neurological score was greatly improved and brain atrophy was greatly reduced in miR-126 modified EPCs-treated SHR rats compared with the control rats 5 weeks after MCAO (P < 0.05). The number of bromodeoxyuridine+/CD31+ microvessels are significantly increased. EPCs migration and proliferation were promoted after miR-126 modified in vitro. Conclusions: Our results showed that miR-126 modified EPCs therapy reduced ischemic brain injury, along with increased angiogenesis and neurogenesis in SHR rats, suggesting miR-126 significantly improved EPCs function in angiogenesis after MCAO. Gene modified EPCs represents a promising avenue for ischemic stroke stem cell therapy.